Socio-Economic Relationship Between Weavers With Small And Medium Industries (SMEs) Bima Weaving - Nurnazmi; Darsono Wisadirana; Siti Kholifah; Anif Fatma Chawa (Technium Social Sciences Journal, 2024)
Weaving (muna) is a result of knowledge, culture, beliefs, natural environment, and the state of the community itself. Weavers establish social relationships with Bima weaving small and medium industries (SMEs) to support their existence in the world of weaving. The social relationships are mutually beneficial and there are adverse effects on the Bima weaving SMEs. Weaving capital is financed by Bima weaving SMEs in the form of money and yarn. Domestic household needs that cause weavers to sell woven fabric production to other weaving SMIs. The research paradigm is constructivism, with a qualitative approach and case study research type. Research on the socio-economic relationship between weavers and Bima weaving SMEs in a single study is a single case study, so this case study uses an embedded design. The technique of determining informants using purposefully select, the main informants are weavers and owners of Bima weaving SMEs, supporting informants are government and community leaders. Data collection techniques are participant observation, open-ended interviews and unstructured interviews, and documentation Data analysis techniques use spiral model data analysis. Data validity testing techniques used triangulation of data sources and data collection methods. The theory used to analyze the research results uses Max Weber’s social action theory. Social relations that exist between weavers and small and medium industries (SMEs) of Bima weaving consist of friendship, openness, empathy, trust, help (sympathy). The economic relationship that emerged was that the Bima weaving SMEs helped weavers in fulfilling domestic household needs, education of weavers’ children, protection of weavers even though the production of woven fabrics was small. The principles of trust and kinship that strengthen economic relations between weavers and Bima weaving SMEs.